Characteristics of Interpretation Teaching in Higher School - Charikova, Iryna; Halapchuk-Tarnavska, Olena M.; Чарікова, Ірина; Галапчук-Тарнавська, Олена Михайлівна (TESOL-Ukraine, 2017)
Interpretation – is not only artistic work but also rather subjective. An author of the textbook on interpretation will hardly ever suggest variants of interpretation as he/she might be criticized. The reason is that there are both a lot of wrong and correct renderings. That is why to learn to interpret means to learn the vocabulary and develop the skill to of understanding synonymic flexibility. Synonymy should not be treated as a set of words similar in meaning belonging to the same part of language but as an ability of any language to express the idea with the help of different means: vocabulary, stylistic devices and contextual «guessing».
Keywords: interpreting teaching; professional interpreter; traits of character; interpreting skills